KRONİK OBSTRÜKTİF AKCİĞER HASTALIĞI OLAN OLGULARDA DÜŞÜK KARBONHİDRAT/ YÜKSEK YAĞ BİLEŞİMLİ BESLENMENİN SOLUNUM FONKSİYONLARINA ETKİSİ - AYDIN TOSUN, Günay; UMUT, Sema; YILDIRIM, Nurhayat; HACIBEKİROĞLU, Atilla; ŞAHİN, Gülderen; YÜCEL, Rifat (Cerrahpaşa Medical Journal, 2014)
Background. The aim of the study was to evaluate the effect of low carbohydrate high fat diet in stable hypercapnic chronic obstructive pulmonary disease (COPD) patients. Design. Respiratory function tests were performed on 14 stable COPD patients on the 1st and 15th days of the study. Activity of accessory respiratory muscles were detected by electromyograms of sternocleidomastoid and external oblique muscles. Patients who received inhalation steroids, inhaler and oral beta 2 agonist and oral teophylline during the study were started on a diet with low carbohydrate and high fat and supported by 500 ml/day liquid diet which contained 16.7% protein, 55.2% fat, 28.1 % carbohydrate, vitamins and minerals (Pulmocare). Results. After 10 days of diet FVC increased (p < 0.05) and PaCO2 decreased (p < 0.05). The activation time of both muscles decreased significantly (p < 0.05). Conclusion. These data indicate that low carbohydrate high fat diet improves respiratory muscle function and decreases CO2 retention.